Basic taxation with the National Internal Revenue Code of the 1997 - Aralar, Reynaldo B. (Mandaluyong City, 2004)
This book is divided into twenty-one (21) chapters, methodically arranged to orient the readers on the carefully chosen topics thereof. The power of taxation, the inherent and constitutional limitations thereon, fundamental aspects in the updated National Internal Revenue Code, Tariff and Customs Code and Local Government Code tax provisions, including jurisprudence on national and local taxation, and other taxation matters beneficial to both people and government are discussed in detail whenever necessary here.
Keywords: Taxation, Philippines